Dante and Polish writers : from Romanticism to the present - Ceccherelli, Andrea (New York, NY : Routledge, 2024)
"Dante and Polish Writers from Romanticism to the Present explores the phenomenon of Polish Danteism from a hermeneutic perspective. The essays shed light on a series of "encounters" of eminent Polish writers with Dante and the Divine Comedy, resulting in original interpretations, creative reworkings, and a wealth of intertextual references testifying to a dialogue that has always been - and still is - alive, not excluding antagonism and bitter controversy. The authors of the essays are all scholars of Polish literature with comparative expertise, teaching in Italian and Polish universities, which ensures a consistently focused point of view on the receptive context and the ways in which it is affected by the confrontation with Dante. The hermeneutic horizon ranges from the Inferno-like reading of the inhuman lands with which history abounds, to the metaphysical yearning underlying Dante's "poetics of transhumanizing", to recent perspectives related to the posthuman and storytelling"--
Keywords: Dante Alighieri, -- 1265-1321 -- Appreciation -- Poland; Dante Alighieri, -- 1265-1321 -- Influence; Dante Alighieri, -- 1265-1321.; Polish literature -- History and criticism; LITERARY CRITICISM / European / Eastern (see also Russian & Former Soviet Union); LITERARY CRITICISM / European / Italian